Body perception of teenagers in school environments - doi:10.5020/18061230.2011.p390 - Valentin Gavídia Catalan; Nathalia Parente de Sousa; Ana Paula Vasconcellos de Abdon; Cristina de Santiago Viana Falcão; Ana Maria Fontenelle Catrib (Universidade de Fortaleza, 2012)
Objective: To assess body perception of teenagers in school environments. Methods: We conducted a qualitative study in a secondary public school from the city of Fortaleza-CE, Brazil, with students from the ninth grade, aged 14 to 16 years old, independent of sex, from March to June, 2009. The first phase consisted of the selection of ten students, using a schematic drawing of the human body. In the second phase, there was a focal group with guiding questions about body awareness and desire for change. Results: For the students, the idea of good posture would be a person who had good education and to be straight when walking and sitting. We perceived dissatisfaction and important misunderstanding in relation to their body and posture, and there was unanimity concerning the desire of achieving changes. Conclusion: There are mixed feelings related to the body, by teenage students, when you inquire about their image and desire to change. If, on one hand, they refer to perceive themselves with proper and correct posture, on the other hand, they are eager for change, easily identified with present standard body reported in the media and worshiped as "ideal body". It is urgent and necessary to consolidate the culture of health promotion in schools as well as build healthy educational environment.